Interventions for Individuals with Low Health Literacy: A Systematic Review - Stacey Sheridan; David J. Halpern; Anthony J. Viera; Nancy D Berkman; Katrina E Donahue; Karen Crotty (2011)
The U.S. Department of Health and Human Services recently called for action on health literacy. An important first step is defining the current state of the literature about interventions designed to mitigate the effects of low health literacy. We performed an updated systematic review examining the effects of interventions that authors reported were specifically designed to mitigate the effects of low health literacy. We searched MEDLINE®, The Cumulative Index to Nursing and Allied Health Literature (CINAHL), PsycINFO, Educational Resources Information Center (ERIC), and the Cochrane Library databases (2003 forward for health literacy; 1966 forward for numeracy). Two reviewers independently reviewed titles, abstracts, and full-text articles for inclusion and included studies that examined outcomes by health literacy level and met other pre-specified criteria. One reviewer abstracted article information into evidence tables; a second checked accuracy. Two reviewers independently rated study quality using predefined criteria. Among 38 included studies, we found multiple discrete design features that improved comprehension in one or a few studies (e.g., presenting essential information by itself or first, presenting information so that the higher number is better, adding icon arrays to numerical information, adding video to verbal narratives). In a few studies, we also found consistent, direct, fair or good-quality evidence that intensive self-management interventions reduced emergency department visits and hospitalizations; and intensive self- and disease-management interventions reduced disease severity. Evidence for the effects of interventions on other outcomes was either limited or mixed. Multiple interventions show promise for mitigating the effects of low health literacy and could be considered for use in clinical practice.